Urine patches indicate yield potential of cocksfoot - Peri, Pablo Luis (2002)
The main yield changes in cocksfoot DM production due to nitrogen (N) from synthetic urine (300 kg N/ha), water stress and regrowth duration in exclosure areas and the dynamics of urine patches (production and crude protein) during all seasons from sheep urine returns in the main grazed area (28 day rotation with 21±1 days regrowth). The application of N (1500 kg N/ha/yr) and five harvests (four 60-days and one 110-days regrowth periods) increased the annual yield by ~14 t DM/ha/yr and irrigation increased annual yield by ~4.4 t DM/ha/yr. The potential growth was recorded for the Canterbury sub-humid temperate environment in irrigated and N fertilised pastures (total annual yield of 28.6 t DM/ha/yr and maximum growth rate of 158 kg DM/ha/d). In the grazed plots, the mean area covered by visually obvious urine patches varied from 25 to 32% with a mean diameter of 0.22 m. The maximum difference in CP% between urine patches and controls was 4.3 units during summer, 7.8 units during winter and 8.3 units during spring. The duration of the effect of urine on DM production and CP% was 56, 112 and 84 days in summer, winter and spring, respectively. Net leaf photosynthesis varied over seasons with a range between 23.5 to 4.5 μmol CO2 m-2 s-1. The leaf photosynthesis analysis indicated that pasture production and duration of urine patches during summer was limited mainly by soil water stress (mean soil volumetric water content in the top 500 mm < 20%) and limited N (< 3 %N). During winter low temperatures (mean daily air temperatures < 9 ºC) limited DM production but determined the longer duration of the effect of urine patches compared with controls.